Towards high potential and ultra long-life cathodes for sodium ion batteries: freestanding 3D hybrid foams of Na7V4(P2O7)4(PO4) and Na7V3(P2O7)4@biomass-derived porous carbon. Issue 15 (1st April 2016) - Li, Qiufeng; Lin, Bo; Zhang, Sen; Deng, Chao
Abstract : Freestanding 3D hybrid foam is a widely applicable, low cost and highly efficient architecture to construct high potential and ultra long life cathodes for sodium ion batteries. Abstract : High potential sodium hosts have attracted enormous attention recently in view of the requirement for improving energy density for sodium ion batteries. Na7 V4 (P2 O7 )4 (PO4 ) and Na7 V3 (P2 O7 )4 with operating potentials near 4.0 V versus Na + /Na are promising cathode candidates. But the low conductivity, limited ion intercalation kinetics and inferior stability remain critical drawbacks for their practical applications. In this paper, the design of freestanding three-dimensional (3D) hybrid foams of high potential sodium hosts@biomass-derived porous carbon is reported. The biological fungus realizes the formation of highly porous graphene-like carbon, which constructs the 3D framework for the high potential polyanions. The polyanion nanocrystals are closely enwrapped by the biomass derived framework and build the hybrid architecture. Both the highly conductive skeleton and the hierarchically porous architecture of hybrid foams are favourable for highly efficient electron and ion transport. Furthermore, the depressed structural deterioration rate and improved contact between the active material and conductive substrate are achieved for the 3D hybrid foams in comparison with the conventional electrodes on the basis of the dynamic studies. Without additional additive or binders, the freestanding hybrid foams achieve desirable characteristics of high operating potentials, fast sodium intercalation and excellent cycling stability. The Na7 V4 (P2 O7 )4 (PO4 )- and Na7 V3 (P2 O7 )4 -based hybrid foams retain 94% and 91%, respectively, of the capacities after 800 cycles at alternative 20C and 3C, demonstrating their superior high rate ultra long-term cycling capability. Therefore, this research provides a low-cost, highly efficient and widely applicable architecture to construct high potential and ultra long-life cathodes for sodium batteries.